Long-term patency of venous conduits targeting the right coronary artery system: single is superior to sequential bypass grafting - Arif, Rawa; Warninck, Aglaia; Farag, Mina; Sommer, Wiebke; Leuschner, Florian; Frey, Norbert; Karck, Matthias; Warnecke, Gregor; Geis, Nicolas (Journal of cardiovascular development and disease, 2022)
Little is known about the fate of bypass grafts to the right coronary system. To investigate the long-term patency of venous bypass grafts directed to the right coronary artery (RCA) based on postoperative angiograms and to identify predictors of graft occlusion.
Gesehen am 15.11.2022